Dataset associated with "Trifluoroacetic acid deposition from emissions of HFO-1234yf in India, China, and the Middle East" - David, Liji M. (Colorado State University. Libraries, 2021)
We have investigated trifluoroacetic acid (TFA) formation from emissions of HFO-1234yf, its dry and wet deposition, and rainwater concentration over India, China, and the Middle East with GEOS-Chem and WRF-Chem models. We estimated the TFA deposition and rainwater concentrations between 2020 and 2040 for four previously published HFO-1234yf emission scenarios to bound the possible levels of TFA. We evaluated the capability of GEOS-Chem to capture the wet deposition process by comparing calculated sulfate in rainwater with observations. Our calculated TFA amounts over the U.S., Europe, and China were comparable to those previously reported when normalized to the same emission. A significant proportion of TFA was found to be deposited outside the emission regions. The mean and the extremes of TFA rainwater concentrations calculated for the four emission scenarios from GEOS-Chem and WRF-Chem were orders of magnitude below the no observable effect concentration. The ecological and human health impacts now and continued use of HFO-1234yf in India, China, and the Middle East are estimated to be insignificant based on the current understanding, as summarized by Neale et al. (2021).
TFA deposition and TFA rainwater concentration simulated by the chemical transport models – GEOS-Chem and WRF-Chem, over India, China, and the Middle East for 2015.
Department of Atmospheric Science
Department of Chemistry
Keywords: HFO-1234yf; Trifluoroacetic acid; wet and dry deposition; India; China; the Middle East